Two-tailed tadpole-shaped synthetic polymer polypeptide bioconjugate nanomicelles for enhanced chemo-photothermal therapy. (16th September 2021) - Augustine, Rimesh; Uthaman, Saji; Kalva, Nagendra; Eom, Kuen Hee; Huh, Kang Moo; Pillarisetti, Shameer; Park, In-Kyu; Kim, Il
Abstract: A series of poly( N -isopropylacrylamide)30 -SS- block -(cyclic-poly( L -lysine)n )- block -SS-poly( N -isopropylacrylamide)30 (n = 10, 20, 30) synthetic polymer polypeptide bio-conjugates have been synthesized for enhanced chemo-photothermal therapy. A combination of reversible addition-fragmentation chain transfer polymerization, click cycloaddition reaction, and ring-opening polymerization of α-amino acid N -carboxyanhydrides is utilized in the synthesis of a tadpole-shaped block copolymer. All the copolymers are self-assembled to nanoparticles in aqueous solutions, which are stabilized using a terephthalaldehyde crosslinker with successfully encapsulating doxorubicin (DOX) and IR780 dye. The polymer nanomicelles exhibited excellent drug loading capacity and efficiency. The in vitro drug release profiles demonstrate that the maximum release of DOX is achieved in pH 5.0 at 42 °C, in the presence of a glutathione intracellular mimic environment. IR780 dye significantly induces photothermal cytotoxicity to HT29 colon cancer lines under near-infrared laser irradiation. The new two-tailed tadpole-shaped synthetic polymer polypeptide bioconjugates exhibiting potential chemo-photothermal therapeutic effect thus appear to be a promising platform for anticancer therapy. Graphical abstract: The tadpole-shaped block copolymer, poly(NIPAM)-SS- b -[ cyclic -poly( L -lysine) n ]- b -SS- poly(NIPAM) forms nanocarriers in the presence of doxorubicin/IR780, exhibiting fascinating antitumor activity via combined chemo-photothermal treatment. Image 1 Highlights: A series of tadpole-like synthetic polymer- block -polypeptide bio-conjugates are prepared. Self-assembled nanoparticles exhibit excellent drug loading capacity and efficiency. The nano-drug shows pH and glutathione responsive anticancer drug delivery. The IR780-encapsulated nanoparticles show promising potential chemo-photothermal therapeutic effect.